Enantioselective cyclopropanation and aziridination catalyzed by copper(II) bis(oxazoline) anchored onto mesoporous materials - Albuquerque, Helio
The preparation of multipurpose asymmetric heterogeneous catalysts based on the immobilization of expensive privileged chiral ligands onto porous supports is essential for their use in industry. The benchmark cyclopropanation of styrene has been performed using a copper(II) complex of a commercial chiral bis(oxazoline) anchored onto ordered mesoporous silica materials (including SBA-15) and their carbon replicas (including CMK-3), and for the first time, we also report on the asymmetric aziridination of styrene by anchored copper(II) bis(oxazoline). All the composites prepared were active and enantioselective in these two organic transformations. In the cyclopropanation of styrene, the best heterogeneous catalyst gave higher enantioselectivities and TON than in the corresponding homogeneous phase reactions. In the aziridination of styrene the enantioselectivities for the best heterogeneous catalysts were similar to the propylated bis(oxazoline). The mesoporous silica, prepared by a straightforward one-pot procedure, was always among the best supports for the functionalized bis(oxazoline) in all the asymmetric processes studied. However its carbon replica was not a good support for the outcome of these asymmetric transformations, always yielding the lowest enantioselectivities. Once again the mesoporous materials surface properties were an important factor for the uniform distribution of the homogeneous catalyst, as well as for the course of the asymmetric organic reactions, together with the pore size. The best results presented herein are comparable to the ones reported for copper(II) bis (oxazoline) (2) immobilized onto other types of porous supports. (C) 2014 Elsevier Ltd. All rights reserved.